O regime de mudanças climáticas: diagnóstico de instrumentos de gestão no âmbito das Nações Unidas e da União Européia - Alberto, Luiz Guilherme Alves (Universidade do Vale do Rio dos Sinos, 2010)
The climate change regime is one of the main themes of the international agenda. The ways in which countries and international organizations are organized in relation to this theme still provides several discussions. In this sense, this paper aims to study this regime, with emphasis on management instruments seen in the United Nations and the European Union. In this way, it is analyzed their effectiveness and the impacts of their efforts to handle climate change. For this purpose, it is studied the concept of global public goods, through the use of the complex interdependence theory in order to understand how the climate fits into this context and how it formed a system to aggregate the instruments. Specifically, this works aims to analyze the studies on adapting and mitigating the effects of climate change and its relevance in the overall management of the problem. It is a fact, however, that although there are advances with systems such as the one in European Union, its activities still need to be increased, so it can be said that it is a management of problems related to the climate.
Keywords: Gestão; Bens públicos globais; Regimes internacionais; Mudanças climáticas; Management; Global public goods; International regimes; Climate change